Investigation Limb darkening for short period AB Andromeda eclipsing binary star - Chiman Ibrahim Hussein Mrs (Polytechnic Journal)
This work deal with characterizing the limb darkening coefficients for the short period binary stars AD Andromeda to determine the size, luminosities and masses of the Individual stars as well as orbital size and orientation of the binary system. Calculate limb darkening for monochromatic pass bounds, the visual rang i.e. intermediate (uvby) have been calculated and broad bands to the near infrared. Also compute bolometric limb darkening coefficients for a linear as well as nonlinear logarithmic and square root limb darkening law as function of surface effective temperatures covering a wide range and surface gravities. By using the interpolation program of Vanhamme.